Data hiding inside JPEG images with high resistance to steganalysis using a novel technique: DCT-M3 - Abdelhamid Awad Attaby; Mona F.M. Mursi Ahmed; Abdelwahab K. Alsammak (Ain Shams Engineering Journal, 2018)
Information security relies mainly upon encryption, and in some cases, steganography for an extra layer of security. Steganography is the science and art of secret communication between two sides that attempts to conceal the existence of the message. Many steganographic techniques have been proposed, all of them make statistically noticeable changes in the properties of the cover carrier particularly when the message payload is high. In this paper, we propose a new methodology of transform domain JPEG image steganography technique that provides high embedding performance while introducing minimal changes in the cover carrier image. The algorithm, named DCT-M3, uses modulus 3 of the difference between two DCT coefficients to embed two bits of the compressed form of the secret message. The proposed algorithm reduces significantly the number of changes in the cover image; the embedding capacity has been improved by 16.7% approximately while maintaining minimum detectability against blind steganalysis schemes. Keywords: Steganography, Steganalysis, Data hiding, LSB, DCT-M3